Spiritual Communication of Selakaran Among Sasak Muslim Community During The Covid-19 Pandemic - Muhammad Syaoki (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2022)
The COVID-19 pandemic has introduced unparalleled challenges to individuals worldwide, resulting in substantial alterations in lifestyles. These alterations encompass the adoption of health protocols, such as social distancing and frequent handwashing. Nevertheless, it is noteworthy that certain Sasak Muslim communities have opted for a distinctive approach in confronting the pandemic. Their chosen strategy revolves around the performance of rituals. These rituals, executed collectively, are perceived by the Sasak Muslim community as a means to counteract the global COVID-19 pandemic. To comprehensively explore the significance of these rituals within the Sasak Muslim community's response to the COVID-19 pandemic, this qualitative research employs an ethnographic approach. The overarching goal is to gain insight into how these rituals are construed and employed by the community. The study's findings unveil that the Sasak Muslim community perceives the pandemic as a typical ailment, one that can be alleviated through a deepened connection with Allah. One of the primary methods through which this closeness is sought is an increased engagement in dhikr, which involves the remembrance of Allah, and prayers performed within the framework of specific rituals such as Selakaran.